Silk fibroin artificial bone as well as preparation method and application thereof
By controlling the freezing process, the problem of mismatch between the degradation rate of existing bone tissue engineering scaffold materials and the tissue regeneration rate is solved, and the high mechanical properties and adjustable biodegradation performance of the silk fibroin scaffold are achieved, simplifying the preparation process and reducing costs.
Patent Information
- Application Number
- CN202411969207.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-25
AI Technical Summary
In the process of improving mechanical properties, existing bone tissue engineering scaffolds ignore the matching problem of material degradation rate and tissue regeneration rate, resulting in increased difficulty in material preparation and increased economic costs.
By controlling the temperature, time and transformation rate during the freezing process, the forces within and between silk fibroin are regulated, and the folding between hydrophobic chains is restricted to form a crystal structure, thereby promoting the generation of intramolecular crystal structures, and obtaining appropriate mechanical properties and adjustable biodegradation rate.
The tunable biodegradable properties of the silk fibroin scaffold are achieved, allowing them to match different tissue growth rates, while improving the mechanical properties and biosafety of the material, simplifying the preparation process and reducing costs.
Smart Images

Figure CN119868651A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silk fibroin artificial bone and a preparation method and application thereof, belonging to the technical field of medical materials. Background Art
[0002] Orthopedic diseases and defects caused by geriatric diseases and accidents are one of the urgent problems to be solved in current medical treatment. Bone transplantation has always been an important treatment for bone regeneration, but problems such as secondary surgery, rejection and infection have resulted in high failure rates for allografts and xenografts. Bone tissue engineering provides a new approach to bone tissue healing and growth. An ideal bone tissue engineering scaffold has a certain mechanical strength and can provide temporary mechanical support at the defect. At the same time, the material itself should have a void structure that allows for the diffusion of nutrients and oxygen, and can promote cell growth and infiltration. In addition, it can integrate the scaffold and tissue and promote bone tissue repair, and degrade and reabsorb over time to match the remodeling rate of the host tissue.
[0003] Silk fibroin is an FDA-approved biomaterial, and its good biocompatibility makes it widely used in in vivo and in vitro tissue engineering materials. Silk fibroin molecules interact to form a crystalline network or nanofiber assembly, which gives it excellent mechanical strength and adjustable degradation properties to match tissue regeneration. Silk fibroin as a raw material can form a variety of scaffold forms including porous materials, and has the potential to be used as a bone repair material.
[0004] At present, bone tissue engineering scaffolds often focus on improving mechanical properties. Various components and cross-linking agents are added to the scaffold materials to mix and modify silk fibroin, which makes it difficult for the material to degrade. The problem of matching the degradation rate of the scaffold material with the tissue regeneration rate is ignored, and the application is limited. At the same time, the addition of various components makes the material preparation more difficult, and the economic and time costs increase. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a silk fibroin artificial bone and a preparation method and application thereof, by controlling the temperature, time and change rate during the freezing process to regulate the forces within and between silk fibroin molecules, restricting the mutual folding of the hydrophobic chains of the silk fibroin molecules to form a crystalline structure, thereby promoting the formation of the intramolecular crystalline structure, and obtaining a silk fibroin scaffold with suitable mechanical properties and adjustable biodegradation rate through simple temperature field regulation.
[0006] To achieve the above object, the present invention is implemented by adopting the following technical solutions: In a first aspect, the present invention provides a method for preparing a silk fibroin artificial bone, comprising: preparing a silk fibroin solution, wherein the concentration of the silk fibroin solution is in the range of 15-50 wt %; The silk fibroin solution is pre-frozen and frozen by regulating the storage temperature, time and temperature change rate to obtain a silk fibroin body; After the silk fibroin body is subjected to gradient vacuum drying once, it is transferred into ultrapure water for immersion, washed, and then subjected to gradient vacuum drying twice to obtain preliminary silk fibroin artificial bone; The preliminary silk fibroin artificial bone is moved into ultrapure water, and after reaching a water saturated state, it is moved into a closed device, evacuated, and then an inert gas is introduced and pressurized to stand still. A continuously increasing pressure is applied under the vacuum state, and the silk fibroin artificial bone is obtained after drying.
[0007] Furthermore, the preparation of the silk fibroin solution comprises: Put the silk into a sodium carbonate aqueous solution and boil it, then take it out, wash it, and wring it dry. Repeat this process several times and then dry the degummed silk. Putting the degummed silk into a lithium bromide solution under a water bath condition, dissolving and stirring to obtain a dissolved solution; The dissolved solution is dispensed into dialysis bags, dialyzed in a flowing water environment, and a silk fibroin solution is obtained after concentration treatment.
[0008] Furthermore, the concentration range of the sodium carbonate aqueous solution is 0.05~2wt%, and the ratio of the silk to the sodium carbonate aqueous solution is 1g:30~100mL; and / or, the temperature range of the water bath condition is 40~90°C, and the stirring time range is 2~5h.
[0009] Further, the concentration process includes: The silk fibroin solution is added to the polyethylene glycol solution for concentration for 1 to 7 days, wherein the concentration range of the polyethylene glycol solution is 20 to 90 wt %; Impurities and bubbles in the concentrated silk fibroin solution are removed by centrifugation. The centrifugation is performed by a refrigerated centrifuge. The centrifugation temperature is 2-6° C. and the centrifugation speed is 6000-9000 rpm / min.
[0010] Further, the pre-freezing includes: The concentrated silk fibroin solution is poured into a mold and subjected to step freezing, wherein the temperature is lowered to -80 to -30°C within 120 to 720 minutes, and each temperature change of 2 to 20°C is a gradient, and the temperature is maintained for 120 to 1440 minutes after step freezing.
[0011] Further, the freezing comprises: The pre-frozen concentrated silk fibroin solution was placed in a -2 to -8°C environment for 6 to 72 hours, and then placed in a -80 to -30°C environment for 2 to 24 hours.
[0012] Furthermore, the primary vacuum drying and the secondary vacuum drying operations are the same, both using a step-by-step temperature increase method, specifically including: Vacuum drying for 300~540min at -45~-35℃; vacuum drying for 300~540min at -35~-25℃; vacuum drying for 300~600min at -25~-15℃; vacuum drying for 300~600min at -15~-5℃; vacuum drying for 300~600min at -5~5℃; vacuum drying for 60~300min at 5~15℃; vacuum drying for 60~300min at 15~25℃.
[0013] Further, the immersion time ranges from 20 to 60 minutes; and / or, the inert gas is nitrogen or argon; and / or, the pressurization parameters include maintaining 3 to 15 MPa for 20 to 60 minutes; and / or, Furthermore, the drying under vacuum and continuously increasing pressure conditions includes gradually increasing the pressure from 0 to 20-30 MPa within 30-180 minutes at a temperature of 20-50° C., a vacuum degree of 80-120 kPa, and a pressure of 80-120 MPa, and maintaining the pressure for 12-72 hours for drying.
[0014] In a second aspect, the present invention further provides a silk fibroin artificial bone prepared by the method for preparing a silk fibroin artificial bone as described in any one of the above items, wherein the silk fibroin artificial bone has an adjustable pore structure inside, and the pore structure is arranged regularly and tightly.
[0015] In a third aspect, the present invention further provides an application of a silk fibroin artificial bone prepared by the method for preparing a silk fibroin artificial bone as described in any one of the above items, including use for repairing oral alveolar bone tissue.
[0016] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention uses silk as the main material, and regulates the forces within and between silk fibroin molecules by controlling the changes in temperature and time during the freezing process, so as to rearrange the molecules in the silk fibroin solution, limit the folding of the hydrophobic chains of the silk fibroin molecules to form a crystalline structure, and thus promote the formation of intramolecular crystalline structures.
[0017] The present invention uses high-pressure inert gas treatment to connect the free water structure in the material in the form of hydrogen bonds to form hydrates, further stabilizing the secondary structure of the material and ensuring that the crystal structure within the silk fibroin molecule will not transform into other secondary structures; vacuum drying can dry the material at a lower temperature to prevent temperature-induced degeneration of silk fibroin artificial bone. High-pressure inert gas treatment and secondary freeze-drying work together to stabilize the secondary structure of silk fibroin while further increasing the content of the crystal structure within the molecule.
[0018] The secondary structure of the silk fibroin artificial bone prepared by the preparation method of the present invention is mainly intramolecular crystallization, which gives the silk fibroin artificial bone adjustable biodegradability and can match the growth rate of different tissues. At the same time, the silk fibroin molecules are interspersed and dispersed to form a stable structure, so that the prepared silk fibroin artificial bone has good mechanical properties and provides growth space and mechanical support for bone tissue repair.
[0019] The silk fibroin artificial bone provided by the invention has simple components, does not require the addition of other complex additives, has biological safety, and has no toxic side effects.
[0020] Compared with the preparation methods of other artificial bone materials, the silk fibroin artificial bone provided by the present invention does not require special procedures, has a simple preparation method, and is suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the structure of silk fibroin artificial bone in one embodiment of the present invention. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention. Example 1
[0023] The embodiment of the present invention provides a method for preparing a silk fibroin artificial bone, comprising the following steps: (1) Degumming: The silk was immersed in a 1 wt% sodium carbonate aqueous solution, wherein the water bath ratio of the silk and the sodium carbonate aqueous solution was 1 g:100 mL; the mixed solution was boiled for 30 min, the silk was taken out, scrubbed with pure water for 3 times, the water was wrung out, the scrubbing-wringing steps were repeated 3 times, and the silk was dried at 60°C for 48 h to obtain the degummed silk.
[0024] (2) Lytic silk-dialysis: Under 65℃ water bath condition, the degummed silk was dissolved in 9.3 M lithium bromide aqueous solution, where the water bath ratio of degummed silk to lithium bromide aqueous solution was 1 g: 5 mL. After dissolution, it was stirred for 3 h, and the obtained solution was divided into dialysis bags and dialyzed with running water for 3 days to obtain silk fibroin (SF) solution.
[0025] (3) Preparation of silk fibroin solution: The solution was concentrated or diluted with pure water to ensure that the silk fibroin content in the final silk fibroin solution was 30 wt %. The solution was stirred on a magnetic stirrer for about 1 h to completely mix the solution and obtain a 30 wt % silk fibroin aqueous solution.
[0026] (4) Pre-freezing: The silk fibroin solution was placed in a mold and then slowly frozen in a low-temperature device to ensure that the temperature dropped from room temperature to -40°C in 240 minutes, with a temperature change of 10°C as a gradient and a holding time of 600 minutes.
[0027] (5) Freezing: The pre-frozen product was slowly heated up to ensure that it took 720 minutes to heat from -40°C to -4°C, then placed for 48 hours, and then kept in a -40°C environment for 6 hours to obtain silk fibroin.
[0028] (6) Gradient vacuum drying: The silk fibroin body was placed in a freeze dryer and vacuum dried according to the following gradient temperature program: -40°C vacuum drying for 540 min, -30°C vacuum drying for 600 min, -20°C vacuum drying for 600 min, -10°C vacuum drying for 600 min, 0°C vacuum drying for 480 min, 10°C vacuum drying for 240 min, and 20°C vacuum drying for 90 min.
[0029] The silk fibroin body was transferred into ultrapure water with a mass ratio of silk fibroin body to ultrapure water of 1:50. After soaking for 30 minutes, it was washed. After repeating 3 times, a second gradient vacuum drying was performed. The above-mentioned gradient vacuum drying operation was repeated to obtain a preliminary silk fibroin artificial bone.
[0030] (7) High-pressure inert gas treatment The preliminary silk fibroin artificial bone was immersed in ultrapure water for 30 minutes to reach a saturated state and then placed in a high-pressure gas reaction device. Nitrogen was introduced after vacuuming and the pressure was maintained at 10 MPa for 30 minutes.
[0031] (8) Vacuum pressure drying The treated silk fibroin artificial bone was moved into a vacuum drying oven, and the pressure was gradually increased from 0 to 20 MPa within 120 min at 30°C and 90 kPa vacuum degree, and the drying was maintained for 48 h to obtain the silk fibroin artificial bone. Figure 1 shown. Example 2
[0032] This embodiment provides a method for preparing a silk fibroin artificial bone, which is basically the same as that of Embodiment 1, except that the concentration of the silk fibroin solution in step 3 is 38%. Example 3
[0033] This embodiment provides a method for preparing a silk fibroin artificial bone, which is basically the same as that of Embodiment 1, except that the concentration of the silk fibroin solution in step 3 is 46%. Example 4
[0034] This embodiment provides a method for preparing a silk fibroin artificial bone, which is basically the same as that of Embodiment 1, except that in step 4, the temperature is cooled from room temperature to -40°C for 120 minutes. Example 5
[0035] This embodiment provides a method for preparing a silk fibroin artificial bone, which is basically the same as that of Embodiment 1, except that in step 4, the temperature is cooled from room temperature to -40°C for 360 minutes. Example 6
[0036] This embodiment provides a method for preparing a silk fibroin artificial bone, which is basically the same as that of Embodiment 1, except that in step 4, the temperature is cooled from room temperature to -20°C for 240 minutes. Example 7
[0037] This embodiment provides a method for preparing a silk fibroin artificial bone, which is basically the same as that of Embodiment 1, except that in step 4, the temperature is cooled from room temperature to -80°C for 240 minutes. Example 8
[0038] This embodiment provides a method for preparing silk fibroin artificial bone, which is basically the same as that of Embodiment 1, except that the method is maintained in a -4°C environment for 12 hours in step 5. Example 9
[0039] This embodiment provides a method for preparing silk fibroin artificial bone, which is basically the same as that of Embodiment 1, except that the method is maintained in a -4°C environment for 24 hours in step 5.
[0040] Comparative Example 1: This comparative example provides a method for preparing a silk fibroin artificial bone, which is basically the same as Example 1, except that in step 4, the bone is directly placed in a -40°C environment without slow cooling.
[0041] Comparative Example 2: This comparative example provides a method for preparing silk fibroin artificial bone, which is basically the same as Example 1, except that in step 5, the silk fibroin is not allowed to stand at -4°C to regulate the intermolecular and intramolecular crystal structures, but is directly frozen and then dried, and then immersed in 99% ethanol solution for water-insoluble treatment and then naturally dried.
[0042] Comparative Example 3: This comparative example provides a method for preparing a silk fibroin artificial bone, which is basically the same as that of Example 1, except that in step 6, no secondary freeze-drying treatment is performed.
[0043] Comparative Example 4: This comparative example provides a method for preparing a silk fibroin artificial bone, which is basically the same as Example 1, except that high-pressure inert gas treatment is not performed in step 7. The performance of Examples 1 to 9 and Comparative Examples 1 to 4 is tested below.
[0044] Comparative Example 5: This comparative example provides a method for preparing a silk fibroin artificial bone, which is basically the same as Example 1, except that in step 8, a forced air drying oven is used for drying, and no pressure is applied during the process.
[0045] The following are performance tests for Examples 1 to 9 and Comparative Examples 1 to 5. Mechanical properties test: The bone powder was pressurized to form a block and cut into a sample size of about 1.5*1.5 cm cylindrical. The compressive strength of the material was tested using a universal material testing machine under the same conditions of a loading speed of 10 mm / min. Five samples were tested for each Example or Comparative Example, and the results are shown in Table 1.
[0046] Table 1: Average maximum compressive strength of the test samples of Examples 1 to 9 and Comparative Examples 1 to 4
[0047] The test results show that the higher the silk protein concentration, the higher the mechanical properties of the scaffold; the slower the cooling rate in the pre-freezing stage, the more time and energy the ice crystals have to form in the same direction during the freezing process. After the ice crystals sublimate, the gaps are arranged more regularly and tightly, and the mechanical properties are better.
[0048] The compressive strength of comparative example 1 is significantly lower than that of embodiments 1, 4, and 5; the pore structure in the scaffold increases by lowering the low-temperature storage temperature, thereby reducing the mechanical properties; low-temperature storage at -4°C is used to regulate the proportion of crystalline structures within and between silk protein molecules. The movement of molecular chains is restricted under low-temperature conditions, resulting in the formation of hydrogen bonds within the molecules, and the molecules interpenetrate with each other to form a crystalline structure, which is the main basis for the water insolubility of the scaffold. As the storage time increases, the proportion of intermolecular structures increases, and the mechanical properties of the scaffold increase.
[0049] In Comparative Example 2, after the water-soluble stent was treated with ethanol to make it insoluble in water, the mechanical properties of the stent were good, but the stent material contained a large amount of intermolecular crystalline structures that were difficult to degrade and did not have biodegradability.
[0050] In Comparative Example 3, no secondary gradient vacuum drying was performed, and the proportion of crystalline structure in the silk fibroin molecule was reduced, which affected the mechanical properties of the overall material.
[0051] In Comparative Example 4, no high-pressure inert gas treatment was performed, and the mechanical properties were slightly reduced. In a high-pressure environment, the inert gas can combine with the free water molecules in the scaffold to stabilize the secondary structure and ensure that the crystalline structure within the silk protein molecule will not transform into other secondary structures.
[0052] In Comparative Example 5, no vacuum pressure drying treatment was performed, and the mechanical properties were slightly lower than those in Example 1. Vacuum drying removed the air to form a negative pressure environment, which prompted the pore structure inside the silk fibroin scaffold to close, improving its mechanical properties. At the same time, pressure was applied to pressurize the scaffold to further improve its mechanical properties.
[0053] Alveolar bones are divided into four categories, of which Class I, Class II and Class III are suitable for transplantation. For example, the mechanical properties of the silk fibroin artificial bone prepared in Example 3 meet the compressive strength requirements of Class I and Class II alveolar bones, and are suitable for use as bone grafting materials in implant surgery for patients with Class II alveolar bones.
[0054] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a silk fibroin artificial bone, characterized in that: include: preparing a silk fibroin solution, wherein the concentration of the silk fibroin solution is in the range of 15-50 wt %; The silk fibroin solution is pre-frozen and frozen by regulating the storage temperature, time and temperature change rate to obtain a silk fibroin body; After the silk fibroin body is subjected to gradient vacuum drying once, it is transferred into ultrapure water for immersion, washed, and then subjected to gradient vacuum drying twice to obtain preliminary silk fibroin artificial bone; The preliminary silk fibroin artificial bone is moved into ultrapure water, and after reaching a water saturated state, it is moved into a closed device, evacuated, and then an inert gas is introduced and pressurized to stand still, and the silk fibroin artificial bone is obtained after drying under vacuum and continuously increasing pressure.
2. The method for preparing silk fibroin artificial bone according to claim 1, characterized in that: The method for preparing the silk fibroin solution comprises: Put the silk into a sodium carbonate aqueous solution and boil it, then take it out, wash it, and wring it dry. Repeat this process several times and then dry the degummed silk. Putting the degummed silk into a lithium bromide solution under a water bath condition, dissolving and stirring to obtain a dissolved solution; The dissolved solution is dispensed into dialysis bags, dialyzed in a flowing water environment, and a silk fibroin solution is obtained after concentration treatment.
3. The method for preparing silk fibroin artificial bone according to claim 2, characterized in that: The concentration range of the sodium carbonate aqueous solution is 0.05-2wt%, and the ratio of the silk to the sodium carbonate aqueous solution is 1g:30-100mL; and / or the temperature range of the water bath condition is 40-90°C, and the stirring time range is 2-5h.
4. The method for preparing silk fibroin artificial bone according to claim 2, characterized in that: The concentration process comprises: The silk fibroin solution is added to a polyethylene glycol solution for concentration for 1 to 7 days, wherein the concentration range of the polyethylene glycol solution is 20 to 90 wt %; Impurities and bubbles in the concentrated silk fibroin solution are removed by centrifugation. The centrifugation is performed by a refrigerated centrifuge. The centrifugation temperature is 2-6° C. and the centrifugation speed is 6000-9000 rpm / min.
5. The method for preparing silk fibroin artificial bone according to claim 1, characterized in that: The pre-freezing comprises: The concentrated silk fibroin solution is poured into a mold and subjected to step freezing, wherein the temperature is lowered to -80 to -30°C within 120 to 720 minutes, and each temperature change of 2 to 20°C is a gradient, and the temperature is maintained for 120 to 1440 minutes after step freezing.
6. The method for preparing silk fibroin artificial bone according to claim 1, characterized in that: The freezing comprises: The pre-frozen concentrated silk fibroin solution was placed in a -2 to -8°C environment for 6 to 72 hours, and then placed in a -80 to -30°C environment for 2 to 24 hours.
7. The method for preparing silk fibroin artificial bone according to claim 1, characterized in that: The primary vacuum drying and the secondary vacuum drying are operated in the same manner, both using a step-by-step temperature increase method, specifically including: Vacuum drying for 300~540min at -45~-35℃; vacuum drying for 300~540min at -35~-25℃; vacuum drying for 300~600min at -25~-15℃; vacuum drying for 300~600min at -15~-5℃; vacuum drying for 300~600min at -5~5℃; vacuum drying for 60~300min at 5~15℃; vacuum drying for 60~300min at 15~25℃.
8. The method for preparing silk fibroin artificial bone according to claim 1, characterized in that: The immersion time ranges from 20 to 60 minutes; and / or, the inert gas is nitrogen or argon; and / or, the pressurization parameters include maintaining 3 to 15 MPa for 20 to 60 minutes; and / or, the drying under vacuum and continuously increasing pressure conditions includes gradually increasing the pressure from 0 to 20-30 MPa within 30 to 180 minutes at a temperature of 20 to 50°C and a vacuum degree of 80 to 120 kPa, and maintaining the drying for 12 to 72 hours.
9. A silk fibroin artificial bone prepared by the method for preparing a silk fibroin artificial bone according to any one of claims 1 to 8, characterized in that: The silk fibroin artificial bone has an adjustable pore structure inside, and the pore structure is arranged regularly and tightly.
10. An application of a silk fibroin artificial bone prepared by the method for preparing a silk fibroin artificial bone according to any one of claims 1 to 8, characterized in that: It includes the repair of different types of oral alveolar bone tissue and the repair of bone defects in non-load-bearing areas.
Citation Information
Cited By
High-strength degradable silk fibroin composite bone bar and preparation method thereof
CN121197525A